DAMPAK PSIKOLOGIS TOKOH ISABELLA DALAM NOVEL ISABELLA KARYA MAULANA MUHAMMAD SAEED DEHLVI - Mutia Anggraini; Abdurahman Abdurahman; Hamidin Hamidin (Faculty of Languages and Arts, Universitas Negeri Padang, 2012)
The purpose of this research is to describe the role and impact of converting psychological character Isabella in the novel Isabella works of Maulana Muhammad Saeed Dehlvi by: (1) aspects of the Id, (2) aspects of the Ego, (3) aspects of the Super Ego. The data of this research are the word, phrase, phrases, and sentences that lead to the converting by Isabella that author expressed in the story. The data resources is founded in the novel itself. The data is collected by using descriptive methode that priorityzing the interaction interconcepts that studied empirically. The result of this research is thebpsychological impact that experienced by Isabella in the novel Isabella caused by id impulse that dominating herself.